2004
DOI: 10.1073/pnas.0402414101
|View full text |Cite
|
Sign up to set email alerts
|

Identification of anthrax toxin genes in aBacillus cereusassociated with an illness resembling inhalation anthrax

Abstract: Bacillus anthracis is the etiologic agent of anthrax, an acute fatal disease among mammals. It was thought to differ from Bacillus cereus, an opportunistic pathogen and cause of food poisoning, by the presence of plasmids pXO1 and pXO2, which encode the lethal toxin complex and the poly-␥-D-glutamic acid capsule, respectively. This work describes a non-B. anthracis isolate that possesses the anthrax toxin genes and is capable of causing a severe inhalation anthrax-like illness. Although initial phenotypic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
537
3
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 444 publications
(570 citation statements)
references
References 34 publications
13
537
3
3
Order By: Relevance
“…However, these results suggest that the increase of BSI in summer was not associated with a specific strain. The contribution of common [3,5,12]. Our study was not able to explain the virulence determinants that affected the clinical presentation.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…However, these results suggest that the increase of BSI in summer was not associated with a specific strain. The contribution of common [3,5,12]. Our study was not able to explain the virulence determinants that affected the clinical presentation.…”
Section: Discussioncontrasting
confidence: 57%
“…The nheABC gene is the major cytotoxic membrane-damaging factor [21]. In B. cereus food-bourne diarrhoeal disease, nheABC was considered as the main virulence factor and was found in more than 90 % of isolates [12,16,22]. nheABC was also dominant in our BSI isolates.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, the LM1212 genome contains genes for PlcR and NprR, which are quorum-sensing regulators specific to the B. cereus group bacteria (Slamti and Lereclus, 2005;Perchat et al, 2011). The sequences of the sensor regulators (PlcR and NprR) and of their cognate peptides (PapR and NprX) from LM1212 were 100% identical to those of B. cereus G9241 (data not shown), a strain encoding the entire anthrax toxin biosynthetic complex and that was responsible for a human anthrax case (Hoffmaster et al, 2004). This is surprising because PlcR-PapR and NprR-NprX are phylogenetically unrelated and these two systems are supposed to have evolved independently (Perchat et al, 2011).…”
Section: Phenotypic and Genetic Characterization Of Lm1212mentioning
confidence: 99%
“…5,6 The main difference between these 672 Virulence Volume 4 Issue 8 species is the presence of unique virulence plasmids. However, data gathered in the last decade have shown that B. cereus strains that contain anthrax-specific pXO-like plasmids exist [7][8][9][10][11][12] which further obscures the much intermixed phylogenetic structure of the B. cereus group. Some PCR-based assays in use for detection of B. anthracis rely on plasmid-encoded targets in conjunction with a chromosomal marker to correctly differentiate pathogenic from apathogenic B. anthracis strains and B. anthracis from non-anthracis Bacillus species, respectively (for a review see ref.…”
Section: Introductionmentioning
confidence: 99%